A dictionary of the history of medicine - Sebastian, Anton (Informa Healthcare, 2011)
This is a unique, extensively illustrated dictionary of terms, people, events, and dates spanning the entire history of medicine. It is a monumental work of scholarship totaling some 700 double-column pages with a large number of rare and exceptional illustrations from many original sources painstakingly compiled over years of far-searching inquiry involving more than 5,000 books and hundreds of journals. It is a major resource of hard-to-find information about notable medical figures, instruments, conditions, procedures, and dates and a storehouse of captivating anecdotes and background material. The book contains a wealth of material for concise historical introductions to a broad range of subjects and is the sine qua non authority on both well and little known facts of medical history. With this single volume-an unprecedented tour de force representing more than 7,000 hours of exhaustive research-clinicians and researchers from all fields of medicine can quickly and easily find authoritative, detailed definitions and descriptions, with dates, of medical terms and of the people and events contributing to the development of medicine from earliest times to the present day. The entries range widely from such as abacterial pyuria to zygote, including Latin and Greek origins of terms, compact biographies with dates, eponymic information of all kinds, and rarely seen drawings and photographs of antique medical instruments and little-known conditions.